Systematic approach for developing as-built schedule for construction project - Zubair Ahmed Memon,; Muhd Zaimi Abd Majid,; Nur Izzi Md. Yusoff,; Mushairry Mustaffar, (2006)
It is widely recognized that construction industry is information intensive and complex industry. However, present trend and proliferations towards multi-participant mega projects have heightened the need for an effective and efficient evaluation and monitoring by stakeholders. A persistent problem in construction has been in documenting changes, which occur in the field, and preparing the as-built schedule. Combining computer vision technology with 3D CAD to produce as-built drawing offers a potential solution. However a recent investigation indicated that there is a lack of systematic and automated evaluation and monitoring in construction projects. The aim of this research is to identify techniques which are used in the construction industry for monitoring and evaluating the actual physical progress and to establish how the current computer technology can be used for monitoring the construction physical progress on site. 3D CAD is increasingly being used as a design tool for construction projects and digital images can be used to provide accurate information needed to document as-built construction schedule. The DCM provides a bridge for storing structural design information in an integrated construction relational database management system that can be shared by a range of computer applications. The DCM model is a part of developing the Tele-Construction base site management system, which retrieves the status of construction work in progress and develop the actual progress bar chart. A pilot study of Car Parking for Larkin Mosque is conducted to check the validity of DCM. The application of DCM model in monitoring the progress enables project management teams to better track and controls the productivity and provides better mechanism for management of project